Do active innovation policies matter? Findings from a survey on the Hong Kong electronics SMEs - Wan-Hsin Liu (Kiel Institute for the World Economy (IfW), 2008)
Since 1997 the Hong Kong (HK) government has markedly changed its role from being a mere institution provider to being an active innovation promoter. As such, it has actively implemented innovation policies that focus especially on creating new funding opportunities and establishing several R&D centres to facilitate information flow and innovation cooperation between universities and industries. One of the industries in which it has been especially active is the electronics industry. Thus this study looks at the electronics industry to examine, using data collected from a questionnaire survey on the HK electronics SMEs, whether these policies have positively affected innovation intensity in HK. The survey findings indicate that there has been an increase in innovation activities in HK, but also that neither the R&D centres nor the universities have played important roles as innovation sources or innovation partners for the HK electronics SMEs. Rather, the main way through which universities and R&D centres support the HK electronics SMEs' innovation activities seems to be the provision of a highly-qualified labour-force transmitting academic knowledge to companies.
Keywords: D21; L60; O31; O33; O38; R10; R28; 330; Electronics; innovation; innovation policy; regional survey; Hong Kong; China; Innovationspolitik; Technologiezentrum; Forschungskooperation; Wirtschaftspolitische Wirkungsanalyse; Elektronikindustrie; Klein- und Mittelunternehmen; Innovation; Hongkong